Adverse events in an integrated home-based treatment program for MDR-TB and HIV in KwaZulu-Natal, South Africa - Brust, James C M; Shah, N Sarita; van der Merwe, Theo L; Bamber, Sheila; Ning, Yuming; Heo, Moonseong; Moll, Anthony P; Loveday, Marian; Lalloo, Umesh G; Friedland, Gerald H; Gandhi, Neel R (Journal of acquired immune deficiency syndromes (1999), 2013)
Most patients with multidrug-resistant tuberculosis (MDR-TB) in South Africa are HIV-infected, but the safety and tolerability of cotreatment are unknown. The authors reviewed all adverse events (AEs) for patients with MDR-TB in a home-based treatment program in rural KwaZulu-Natal. Of 91 MDR-TB patients, 74 (81%) were HIV-positive and receiving antiretroviral therapy. AEs were common, but most were mild and did not require therapy modification. The most common severe AEs were hypothyroidism (36%) and psychosis (5%). Patients receiving concurrent antiretroviral therapy did not experience AEs more frequently than those on MDR-TB therapy alone. Concurrent treatment for MDR-TB/HIV can be safely administered in a home-based care setting.